Effect of change in microstructures due to simulation temperatures on the low cycle fatigue behavior of P91 steel. (November 2020) - Mariappan, K.; Shankar, Vani; Bhaduri, A.K.
Abstract: In this study, the microstructures of the three principal heat-affected zones (HAZs) of the P91 steel weld joint were simulated using appropriate heat treatments at different soaking temperatures ranging from 865 °C to 1200 °C. Low cycle fatigue tests were conducted on the samples of each microstructural zone of the weld joint at 550 °C employing a constant strain amplitude of ±0.6% and strain rate of 3 × 10 −3 s −1 . In the weld joint's microstructures, the weld metal exhibits the lowest fatigue life, followed by the inter-critical (IC). However, the actual weld joint specimen failed at the interface between the ICHAZ and the base metal.